THE USEFULL OF AUGMENTED REALITY OVER THE NATIONAL INSIGHT IN LEARNING ERA DISRUPTION-BASED - Rochmah, Eliya; Labudasari, Erna; Amalia, Nurani (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Technological progress greatly affects all areas of human life, including in the field of Education. One use of technology in education that can be used is augmented reality that displays a virtual world into a real form that can be more easily understood and fun. Augment reality is used in learning history that is displayed in real way so it can facilitate students in learning. This technology is used to solve problems in learning that students feel bored with learning history that only uses lecture and discussion methods so that students are not eager in learning. In the face of this technological progress is utilized as an innovative form based on disrupsi era so that students can learn history more easily and can appreciate the services of heroes and not forget the history of the nation along with the times. The study was conducted at SDN Kanggraksan class VB with learning outcomes experienced improvement in each cycle.